Secure RFID authentication schemes based on security analysis and improvements of the USI protocol - Gao, Lijun (2019)
Wireless radio frequency identification (RFID) has been widely used as the core technology of the Internet of Things, but it also brings many potential security risks. In this paper, two typical RFID security authentication protocols are analyzed in depth. The results show that the two protocols have security risks, and two targeted attack methods are proposed. Next, two RFID security authentication protocols which can resist the DoS, replay, and tracing attacks are designed. The first protocol uses index grouping and dynamic renewal mechanism. Since the Rabin public key encryption algorithm verification only requires square and modulo operations, the second protocol introduces the public key encryption algorithm into the cost-sensitive RFID tag, and formally verifies the functionality of the proposed scheme by SPIN. Furthermore, the security of the protocol is proven by the BAN logic. The grouping index method can effectively improve the ability to locate tags in a large database and enhance the practicability of the protocol. The introduction of the Rabin public key algorithm improves the security of the protocol under the condition of cost control.